POTENSI NUTRASETIKAL SEBAGAI TERAPI PENDAMPING KANKER PAYUDARA: TELAAH SISTEMATIS - Putri, Sefanadia; Siregar, Mukhlidah Hanun; Suryana, Suryana; Rimbawan, Rimbawan (Universitas Sultan Ageng Tirtayasa, 2025)
Globally, breast cancer stands as the most common cancer and the leading cause of death for women. Currently, breast cancer treatment strategies focus more on the evaluation of clinical and pathological parameters rather than gene expression criteria. With advances in medical science and nutrition, great attention is being paid to foods and natural products that can improve health. Bioactive nutrients that provide protective benefits against breast cancer include polyphenols, retinoids, and polyunsaturated fatty acids (PUFAs). These compounds possess antioxidant, anti-inflammatory, immunomodulatory, and antitumor properties. Specific substances such as resveratrol, epigallocatechin 3-gallate, retinoids, and omega-3 PUFAs influence the characteristics of breast cancer and are involved in various cancer processes, including cell growth inhibition, inflammation, and angiogenesis.